ドームフジ カンソク ケイカク (1991-2007) ニオケル セッピョウ キショウ カンソク ノ ガイヨウ - 高橋, 修平; タカハシ, シュウヘイ; 亀田, 貴雄; カメダ, タカオ; 本山, 秀明; モトヤマ, ヒデアキ; Takahashi, Shuhei; Kameda, Takao; Motoyama, Hideaki (2008)
P(論文) 本報告は,1991年から2007年(第32次南極地域観測隊から第48次隊)に東南極氷床の内陸域に位置するドームふじ基地を中心として実施された「ドームふじ観測計画」で得られた雪氷・気象観測の主要な成果を取りまとめたものである.現地での雪氷・気象観測は,「基本観測」及び「研究観測」として実施された.前者は,ドームふじ観測計画として立案したものであり,後者は南極地域観測隊に参加した研究者が立案したものである.2001年から2007年(第42次隊から第48次隊)まで実施された第二期ドームふじ観測計画期間での基本観測については,観測方法及び現地での観測実施状況を詳しく述べた.なお,ドームふじ観測計画により得られた雪氷・気象観測結果を報告する論文・報告は現在までに157編,学会等での口頭・ポスター発表は243件であった. This paper describes the main results on glaciological and meteorological observations during the Dome Fuji Project held at East Dronning Maud Land, East Antarctic ice sheet, from 1991 to 2007. The project was carried out as Dome Fuji Project I (1991-2000) and Dome Fuji Project II (DFII, 2001-2007). In the Dome Fuji Projects, glaciological and meteorological observations were carried out as "Project observations" and a "Research observations". The former was carried out as part of the Dome Fuji Project, and the latter was carried out by interested researchers who worked in the Dome Fuji area during the project. Observational methods and research schedules during the DFII are described in detail. The number of research papers and reports during the whole Dome Fuji Project is 157, and the numbers of presentations at symposia, conferences or meetings is 243. departmental bulletin paper